Clinical Tolerogenic Dendritic Cells: Exploring Therapeutic Impact on Human Autoimmune Disease - Phillips, Brett Eugene; Garciafigueroa, Yesica; Trucco, Massimo; Giannoukakis, Nick (Frontiers in Immunology, 2017)
Tolerogenic dendritic cell (tDC)-based clinical trials for the treatment of autoimmune diseases are now a reality. Clinical trials are currently exploring the effectiveness of tDC to treat autoimmune diseases of type 1 diabetes mellitus, rheumatoid arthritis, multiple sclerosis (MS), and Crohn’s disease. This review will address tDC employed in current clinical trials, focusing on cell characteristics, mechanisms of action, and clinical findings. To date, the publicly reported human trials using tDC indicate that regulatory lymphocytes (largely Foxp3+ T-regulatory cell and, in one trial, B-regulatory cells) are, for the most part, increased in frequency in the circulation. Other than this observation, there are significant differences in the major phenotypes of the tDC. These differences may affect the outcome in efficacy of recently launched and impending phase II trials. Recent efforts to establish a catalog listing where tDC converge and diverge in phenotype and functional outcome are an important first step toward understanding core mechanisms of action and critical “musts” for tDC to be therapeutically successful. In our view, the most critical parameter to efficacy is in vivo stability of the tolerogenic activity over phenotype. As such, methods that generate tDC that can induce and stably maintain immune hyporesponsiveness to allo- or disease-specific autoantigens in the presence of powerful pro-inflammatory signals are those that will fare better in primary endpoints in phase II clinical trials (e.g., disease improvement, preservation of autoimmunity-targeted tissue, allograft survival). We propose that pre-treatment phenotypes of tDC in the absence of functional stability are of secondary value especially as such phenotypes can dramatically change following administration, especially under dynamic changes in the inflammatory state of the patient. Furthermore, understanding the outcomes of different methods of cell delivery and sites of delivery on functional outcomes, as well as quality control variability in the functional outcomes resulting from the various approaches of generating tDC for clinical use, will inform more standardized ex vivo generation methods. An understanding of these similarities and differences, with a reference point the large number of naturally occurring tDC populations with different immune profiles described in the literature, could explain some of the expected and unanticipated outcomes of emerging tDC clinical trials.